2015
DOI: 10.1589/jpts.27.2675
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography of symmetrical trunk movements and trunk position sense in chronic stroke patients

Abstract: [Purpose] To explore the differences in bilateral trunk muscle activation between chronic stroke patients and healthy controls, this study investigated the symmetry index and cross-correlation of trunk muscles during trunk flexion and extension movements. This study also assessed the differences in trunk reposition error between groups and the association between trunk reposition error and bilateral trunk muscle activation. [Subjects and Methods] Fifteen stroke patients and 15 age- and gender-matched healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…In this study, the perception of seven positions of the trunk in the anteroposterior direction while sitting was investigated. Almost all previous studies have adopted only one or two target positions and a starting position to investigate the trunk position perception 9 , 10 , 11 , 12 ) . However, our study adopted a method in which participants were instructed to stand up right after referencing the target position instead of returning to the starting position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the perception of seven positions of the trunk in the anteroposterior direction while sitting was investigated. Almost all previous studies have adopted only one or two target positions and a starting position to investigate the trunk position perception 9 , 10 , 11 , 12 ) . However, our study adopted a method in which participants were instructed to stand up right after referencing the target position instead of returning to the starting position.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the accuracy of the perception during various trunk positions while seated is necessary to investigate the anticipatory postural control in accordance with various sitting positions. It has been shown that the perception of the trunk position in stroke patients is lower than that in normal subjects based on the reproducibility of the trunk position in a sitting posture 9 , 10 ) . The reproducibility of the lumbar position in low back pain patients has also been investigated 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to perceive one’s own body position accurately. Several reports have examined the perception of the trunk position while sitting, including the subjective postural vertical (SPV)4,5,6 ) and trunk position perception7, 8 ) . The SPV is the perception of body verticality4,5,6 ) , in which somatosensory information has been suggested to have an important role.…”
Section: Introductionmentioning
confidence: 99%
“…The SPV is the perception of body verticality4,5,6 ) , in which somatosensory information has been suggested to have an important role. The trunk position perception, also known as the “trunk position sense”, has been assessed in studies based on the accuracy of the perceived trunk position on the sagittal plane7, 8 ) . Trunk repositioning error has been used to evaluate the trunk position sense7, 8 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation